ab initio Study of Restricted Rotation in N-Nitroso-azirine and N-Nitroso-diaziridine - Kiani, Farhoush; Yeganegi, Saeed; Ali Rostami, Abbas; Sharifi, S. (Asian Journal of Chemistry, 2010)
Ground state and transition state structures, thermodynamic energies, dipole moments, rotational barrier energies around the N-N bond have been determined using density functional theory based method at the B3LYP/6-31G(d,p) level of theory, using Gaussian 98 package programs. There are two equivalent ground state conformers, A and D in N-nitrosoazirine. The rotational energy barrier of nitroso group is calculated to be 13.14 kJ/mol. There are two equivalent ground state conformers, A and C in N-nitroso-diaziridine. The rotational energy barrier of nitroso group is calculated to be 19.71 and 12.05 kJ/mol. In this work, the inversion energy barrier of nitroso group was also calculated as 23.60, 29.41 and 40.42 kJ/mol for N-nitroso-azirine and N-nitroso-diaziridine, respectively.